2022
DOI: 10.3389/fcvm.2022.1007118
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in developing countries: An update

Abstract: IntroductionDespite advances in diagnostic and treatment, morbidity and mortality due to infective endocarditis (IE) has not decreased. There is a discrepancy in epidemiology of IE between developed and developing countries. Over the last years, increased early detection and consequently prevalence of rheumatic heart disease (RHD) and congenital heart disease (CHD) which are considered predisposing conditions for IE, is noted. Here, we present a review of literature on IE in developing countries.MethodsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Due to various morphological and functional changes that occur during blood storage, such as reduced deformability, in ammation, consumption of 2,3-diphosphoglycerol, release of free hemoglobin, and decreased bioavailability of nitric oxide, red blood cell infusion cannot restore su cient microcirculation oxygenation. [27] We also identi ed a signi cant positive correlation between preoperative aortic insu ciency and ventilation dependency following cardiac surgery , and the cut-off value of preoperative aortic insu ciency of 5.25 cm 2 with 100% sensitive and 64.6% speci c for the diagnosis of ventilation dependency. Endocarditis is the most common cause of acute regurgitation in aortic valve.…”
Section: Discussionmentioning
confidence: 77%
“…Due to various morphological and functional changes that occur during blood storage, such as reduced deformability, in ammation, consumption of 2,3-diphosphoglycerol, release of free hemoglobin, and decreased bioavailability of nitric oxide, red blood cell infusion cannot restore su cient microcirculation oxygenation. [27] We also identi ed a signi cant positive correlation between preoperative aortic insu ciency and ventilation dependency following cardiac surgery , and the cut-off value of preoperative aortic insu ciency of 5.25 cm 2 with 100% sensitive and 64.6% speci c for the diagnosis of ventilation dependency. Endocarditis is the most common cause of acute regurgitation in aortic valve.…”
Section: Discussionmentioning
confidence: 77%
“… 26 - 29 Recently reported that the annual number of IE cases worldwide has exceeded 1 million and the number of deaths has exceeded 66 thousand. 30 Scientific databases such as PubMed, Scopus, and WoS show a dramatic increase in the number of articles published in recent years. The increasing importance of IE, which threatens public health, has made bibliometric studies on this subject and the determination of the relevant trends necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The priority should always be the diagnosis, as IE has the risk of spreading to every tissue when the patient has IE suspicion. 34 The diagnosis can be difficult in most cases and may need a combined clinical examination, microbiologic evaluation, and echocardiographic evaluation. New microbiologic and imaging techniques are required, especially in cases with negative blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis is associated with multiple complications, namely neurologic, cardiac, and septic emboli; immune reactions; and metastatic infection. Additionally, infective endocarditis has high mortality and morbidity, and despite improving diagnostic and treatment tools, the incidence is rising worldwide [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%